A semi high-throughput whole blood-based flow cytometry assay to detect and monitor Bordetella pertussis-specific Th1, Th2 and Th17 responses - Corbière, Véronique; Lambert, Eleonora E.; Rodesch, Marine; van Gaans-van den Brink, Jacqueline A. M.; Misiak, Alicja; Simonetti, Elles; Van Praet, Anne; Godefroid, Audrey; Diavatopoulos, Dimitri A.; van Els, Cécile A. C. M.; Mascart, Françoise; , PERISCOPE WP5 Task 7 working group (Frontiers in Immunology, 2023)
The characterization of B. pertussis (Bp) antigen-specific CD4+ T cell cytokine responses should be included in the evaluation of immunogenicity of pertussis vaccines but is often hindered by the lack of standardized robust assays. To overcome this limitation, we developed a two-step assay comprising a short-term stimulation of fresh whole blood with Bp antigens and cryopreservation of the stimulated cells, followed later on by batch-wise intracellular cytokine analysis by flow cytometry. Blood samples collected from recently acellular (aP) vaccine boosted subjects with a whole-cell- or aP-primed background was incubated for 24 hrs with Pertussis toxin, Filamentous hemagglutinin or a Bp lysate (400µl per stimulation). Antigen-specific IFN-γ-, IL-4/IL-5/IL-13-, IL-17A/IL-17F- and/or IL-22-producing CD4+ T cells were quantified by flow cytometry to reveal Th1, Th2, and Th17-type responses, respectively. The frequencies of IFN-γ-producing CD8+ T cells were also analysed. We demonstrate high reproducibility of the Bp-specific whole blood intracellular staining assay. The results obtained after cryopreservation of the stimulated and fixed cells were very well correlated to those obtained without cryopreservation, an approach used in our previously published assay. Optimization resulted in high sensitivity thanks to very low non-specific backgrounds, with reliable detection of Bp antigen-specific Th1, Th2 and Th17-type CD4+ T cells, in the lowest range frequency of 0.01-0.03%. Bp antigen-specific IFN-γ+ CD8+ T lymphocytes were also detected. This test is easy to perform, analyse and interpret with the establishment of strict criteria defining Bp antigen responses. Thus, this assay appears as a promising test for evaluation of Bp antigen-specific CD4+ T cells induced by current and next generation pertussis vaccines.